Factors Influencing Smallholder Farmers’ Decision to Abandon Introduced Sustainable Land Management Technologies in Central Ethiopia - Taye Alemu Mamo; Degefa Tolossa; Feyera Senbeta; Tesfaye Zeleke (Universitas Sebelas Maret, 2022)
The Ethiopian government has made efforts to rehabilitate degraded lands using a range of sustainable land management (SLM) initiatives. One of the key components was the use of improved structural soil and water conservation (SWC) technologies. However, the effectiveness of technology adoption varies greatly among households and abandoning previously accepted measures is a typical occurrence. Thus, this study sought to discover factors influencing smallholder farmers’ decisions to abandon already accepted SWC measures. The analysis was conducted based on data collected from 525 sample households surveyed in two districts in Central Ethiopia. An ordered cumulative logistic (POM) regression model was used to examine variables explaining households’ decision behavior. The study findings have revealed that sampled households were at different adoption stages, i.e., dis-adopters (22%), pilot-level adopters (14%) and adopters (64%). The results from the POM model also show that a range of variables influenced farmers’ dis-adoption decisions. Factors such as awareness about the risks of land degradation, access to training, incentives, land fragmentation, gender, full-time labor size, gentle slope plots, economic returns on investment and post-adoption follow-up were found to substantially influence smallholder farmers’ adoption discontinuance decisions. Thus, policymakers should consider these variables in designing strategies to overcome barriers to SLM practices.